Alpha‐synuclein repeat variants and survival in Parkinson's disease. Issue 8 (27th February 2014) - Chung, Sun Ju; Biernacka, Joanna M.; Armasu, Sebastian M.; Anderson, Kari; Frigerio, Roberta; Aasly, Jan O.; Annesi, Grazia; Bentivoglio, Anna Rita; Brighina, Laura; Chartier‐Harlin, Marie‐Christine; Goldwurm, Stefano; Hadjigeorgiou, Georgios; et al.
ABSTRACT Objectives To determine whether α‐synuclein dinucleotide repeat (REP1) genotypes are associated with survival in Parkinson's disease (PD). Methods Investigators from the Genetic Epidemiology of Parkinson's Disease Consortium provided REP1 genotypes and baseline and follow‐up clinical data for cases. The primary outcome was time to death. Cox proportional hazards regression models were used to assess the association of REP1 genotypes with survival. Results Twenty‐one sites contributed data for 6, 154 cases. There was no significant association between α‐synuclein REP1 genotypes and survival in PD. However, there was a significant association between REP1 genotypes and age at onset of PD (hazard ratio: 1.06; 95% confidence interval: 1.01‐1.10; P value = 0.01). Conclusions In our large consortium study, α‐synuclein REP1 genotypes were not associated with survival in PD. Further studies of α‐synuclein's role in disease progression and long‐term outcomes are needed. © 2014 International Parkinson and Movement Disorder Society